Community Coping Strategies for Protecting Health During Waterlogging Disasters: A Sociological Perspective from the Indus River Region of Sindh - Bhutto, Shahnaz; Talpur, Basit Ali; Alam, Sunana; Akhtar, Farhan (Symbiohealth, 2025)
Waterlogging is a recurring public health and environmental challenge in the lower Indus River region of Sindh, where stagnant water creates widespread health risks and disrupts daily life. This study examines the coping strategies adopted by local communities to protect their health during waterlogging disasters. A mixed-methods approach was employed, combining quantitative data from 300 households with qualitative insights from 30 interviews and focus group discussions. Quantitative findings show that diarrhea (71.3%), skin infections (59.3%), and malaria (52%) were the most commonly reported health problems. The most widely used coping practices included the use of ORS (72.3%), mosquito nets or coils (67.7%), and boiling drinking water (63%). Regression analysis revealed significant predictors of effective coping, including income level (B = 0.21, p = 0.001), education (B = 0.17, p = 0.004), social support (B = 0.29, p < 0.001), and access to healthcare (B = 0.14, p = 0.030), collectively explaining a meaningful proportion of coping effectiveness. Qualitative findings further indicated that community support, traditional remedies, economic hardship, and perceived government neglect strongly shape how residents respond to waterlogging. Overall, the study highlights the need for public health policies that integrate community knowledge, address structural barriers, and strengthen local resilience in disaster-affected regions.